Residents satisfaction towards affordable housing (rumah mampu milik Johor) in Kluang, Johor / Nur Shahidah Mohd Zailan and Thuraiya Mohd - Mohd Zailan, Nur Shahidah; Mohd, Thuraiya (2023)
The provision of affordable housing in Malaysia is increasing as to response to the encouragement of home ownership to all Malaysian by the government specifically for middle- and lower-income group. However, most of the affordable housing provided does not meet the requirement of a good quality of housing. Thus, this research aims to investigate the resident’s satisfaction towards affordable housing and embarks on the objectives which are to identify the elements of residential satisfaction for affordable housing and to determine the level of resident’s satisfaction on the physical and social dimension. This research applies cross sectional research design based on the case study approach. Questionnaire forms were distributed to residents of Rumah Mampu Milik Johor (RMMJ), Taman Kluang Indah involved 182 respondents. The data was analysed quantitively using descriptive statistics involving frequency distribution and percentages and presented in the form of tables for univariate analysis by adopting SPSS software. Findings indicate that, for physical dimension, the residents of RMMJ there are most satisfied with the natural ventilation lighting of the housing units. Meanwhile on the social dimension, the community of the neighbourhood is the main level of resident satisfied. Findings from this research beneficial to housing developers, housing policy maker such as the Housing Local Government Ministry in implementing a specified planning standard for affordable housing development in future and applies various improvement in garnering increased satisfaction levels regarding the overall condition and features their living area; indirectly ensuring investment committed by the residents is worthwhile.